de Haas-van Alphen studies and Fermi surface properties of organic superconductors (ET)[sub 2]X - Wosnitza, J. (Karlsruhe Univ. (T.H.) (Germany). Physikalisches Inst.); Crabtree, G. W.; Williams, J. M.; Wang, H. H.; Carlson, K. D.; Geiser, U. (Argonne National Lab., IL (United States)) (Argonne National Laboratory, 1993)
de Haas-van Alphen (dHvA) measurements of organic superconductors (ET)[sub 2]X, where ET stands for bis(ethylene)dithiotetrathiafulvalene (or BEDT-TTF) and X = IBr[sub 2], (NH[sub 4])Hg(SCN)[sub 4] and Cu(NCS)[sub 2] are reported. The strong two-dimensionality of the Fermi surface (FS) is clearly seen by the perfect 1/cos([Theta])-behavior of the dHvA frequency. The distinctive kind of beating and the angular dependence of the dHvA signal in [beta]-(ET)[sub 2]IBr[sub 2] gives clear evidence for a lightly corrugated structure of the FS. Due to the nearly cylinder-shape of the FS the bare band structure effective mass, m[sub b], also shows a 1/cos([Theta])-dependence which is responsible for spin splitting zeros at certain angles. At these points, where the fundamental amplitude of the dHvA signal is vanishing, m[sub b] could exactly be determined and by comparison with the independently measured cyclotron effective mass the electron-phonon coupling constant could be estimated. 17 refs, 5 figs.